IDENTIFIKASI SEKTOR UNGGULAN DAN KETIMPANGAN ANTARKABUPATEN/KOTA DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - ., Restiatun (Jurnal Ekonomi & Studi Pembangunan, 2009)
This study aims to identify the leading sectors in each district/city in the province of Yogyakarta Special Region. In addition, analysis of the disparities between districts was also discussed in this study. This study using Location Quotient approach, Typology Klassen, Williamson index and Theil Entropy Index. The results showed that there is a tendency that this disparity increased over time, the city of Yogyakarta in the regional classification fast forward and fast growing, whereas the districts of Bantul and Kulon Progo, including in relatively remote areas classification. DIY Province rising trend imbalances occur. The calculated ratio of the highest per capita income and lowest regions in the Province of DIY shows the trend of improvement.